Comparative effectiveness of dulaglutide versus liraglutide in Asian type 2 diabetes patients: a multi-institutional cohort study and meta-analysis - Kai-Cheng Chang; Shih-Chieh Shao; Shihchen Kuo; Chen-Yi Yang; Hui-Yu Chen; Yuk-Ying Chan; Huang-Tz Ou (Cardiovascular Diabetology, 2020)
Abstract Background Head-to-head comparison of clinical effectiveness between dulaglutide and liraglutide in Asia is limited. This study was aimed to assess the real-world comparative effectiveness of dulaglutide versus liraglutide. Methods We conducted a retrospective cohort study by utilizing multi-institutional electronic medical records to identify real-world type 2 diabetes patients treated with dulaglutide or liraglutide during 2016–2018 in Taiwan and followed up until 2019. Effectiveness outcomes were assessed at every 3 months in the 1-year follow-up. Propensity score techniques were applied to enhance between-group comparability. Significant differences in changes of effectiveness outcomes between treatment groups during the follow-up were examined and further analyzed using mixed-model repeated-measures approaches. Results A total of 1512 subjects receiving dulaglutide and 1513 subjects receiving liraglutide were identified. At 12 months, significant HbA1c changes from baseline were found in both treatments (dulaglutide: − 1.06%, p < 0.001; liraglutide: − 0.83%, p < 0.001), with a significant between-group difference (− 0.23%, 95% confidence interval − 0.38 to − 0.08%, p < 0.01). Both treatments yielded significant declines in weight, alanine aminotransferase level, and estimated glomerular filtration rate from baseline (dulaglutide: − 1.14 kg, − 3.08 U/L and − 2.08 mL/min/1.73 m2, p < 0.01; liraglutide: − 1.64 kg, − 3.65 U/L and − 2.33 mL/min/1.73 m2, p < 0.001), whereas only dulaglutide yielded a significant systolic blood pressure reduction (− 2.47 mmHg, p < 0.001). Between-group differences in changes of weight, blood pressure, and liver and renal functions at 12 months were not statistically significant. Conclusions In real-world T2D patients, dulaglutide versus liraglutide was associated with better glycemic control and comparable effects on changes of weight, blood pressure, and liver and renal functions.